2021
DOI: 10.3390/su14010117
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Mapping of Research Trends on Financial Behavior for Sustainability

Abstract: This article presents a global empirical overview of studies on financial behavior in relation to education, money-saving, and consumption, contributing to research on the Sustainable Development Goals (SDGs) related to social equity in the quality education (4th Sustainable Development Goal) and inequality reduction (10th Sustainable Development Goal) areas. Thus, the data and metadata of 492 articles registered between 1992 and August 2021 were extracted from the Web of Science (Journal Citation Report, JCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 102 publications
0
11
0
5
Order By: Relevance
“…This research followed the design of a descriptive bibliometric analysis to perform a scientific mapping of scientific publications on PA and BC similar to those used in other research (26)(27)(28)(29).…”
Section: Designmentioning
confidence: 99%
“…This research followed the design of a descriptive bibliometric analysis to perform a scientific mapping of scientific publications on PA and BC similar to those used in other research (26)(27)(28)(29).…”
Section: Designmentioning
confidence: 99%
“…The analysis revealed the category distribution, the most influential articles, the top research areas, the prominent supportive funding agencies and the future research direction in the scientific field of financial risk management. López-Medina et al (2022) presented a macroscopic overview of research on financial behavior in relation to individuals’ educational level, consumption, and money-saving, making contributions to the study concerning the sustainable development goals (SDGs). The data of 492 articles were retrieved from WoS during the time span of 1992 to 2021, and were visualized via VOSviewer software.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The overview of the literature showed that abundant research on FDM has explored the factors impacting FDM process, and that prior bibliometric studies have explored the relation between behavioral finance and financial/managerial decision making, but only focused on the effects of certain cognitive biases, like overconfidence, confirmation bias and anchoring effect ( Costa et al, 2017 ). Other studies either explored the domain of behavioral finance in relation to individuals’ decision making ( Costa et al, 2018 ) or the effects of financial literacy on savings and consumption decisions as well as investment decision making ( López-Medina et al, 2022 ). In addition, the bibliometric analysis of financial risk management which can play a role in FDM was also conducted ( Ahmad et al, 2021 ).These studies provided important insights into the further investigation of financial decision-making process, but the overall profile of the FDM research still awaits investigation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A alfabetização financeira, decorrente da internalização de elementos da educação financeira, é considerada uma habilidade essencial para a vida adulta, dada a conjuntura social, política e econômica contemporânea (Huston, 2010;Potrich, Vieira, & Kirch, 2015). O tópico vem ganhando relevância na comunidade científica, evidenciado através do crescimento exponencial das produções científicas nas últimas décadas (López-Medina et al, 2021;Couto, Maracajá & Machado, 2022).…”
Section: Revisão Da Literaturaunclassified
“…Por fim, o quarto bloco é o que possui o menor volume de pesquisas e suas investigações discutem a educação financeira de uma forma mais interdisciplinar; é justamente neste bloco onde as discussões envolvendo a sustentabilidade se concentram (Lyons, Rachlis & Scherpf, 2007;Brennan & Coppack, 2008;Hira, 2012;Kindle, 2010;2013;Helm et al, 2019;Anderson et al, 2013;Ianole et al, 2020;López-Medina, 2021).…”
Section: Revisão Da Literaturaunclassified